TÍNH THÔNG SỐ TẦNG CHỨA NƯỚC THEO TÀI LIỆU CAROTA ĐẠT HIỆU QUẢ CAO TRONG THIẾT KẾ, XÂY DỰNG GIẾNG KHAI THÁC NƯỚC TẦNG SÂU Ở ĐỒNG BẰNG SÔNG CỬU LONG - Bàng, Nguyễn Hồng (Vietnam Journal of Earth Sciences, 2011)
Aquifer parameter calculation by well logging data - a highly effective method in design, construction of deep water production well in Cuu Long Plain Currently, in Cuu Long River Delta, exploration and abstraction of deep groundwater is more interested due to saline and contaminated surface water and overexploitation of shallow groundwater that causes water level in some zones to be decreased. Complication in distribution of fresh and saline ground water by depth in the area and hazards in deep water exploration and production require applying advanced digital technologies and equipments in well logging and borehole geophysical data processing. New hydrogeologic probe allows logging 4 normal resistivity measurements (8, 16, 32 and 64 inch), as well as single point resistance (R), spontaneous potential (SP), natural gamma (GR), fluid temperature and fluid resistivity (Rm). Geophysical parameters allow to calculate some aquifer parameters such as porosity Φ, total dissolved solids M or chloride content of groundwater. The results have been contributed effectively in design and construction of deep water production wells in Cuu Long river delta.